Frequency and Clinical Features of Guillain Barré Syndrome Among Patients of University of Science and Technology Hospital from 2014 to 2023, Sana'a, Yemen, 2023 - Al-Fotaihi, Eissa Sadeq; Murait, Rasheed Dares; Waza'a, Osama Fhami; Al-Haddad, Amgad Saddam; Danamh, Khalid Muthanna; Al-Zedar, Bassam Ali (My University, 2023)
Background: GBS is a rare neurological disorder that affects the peripheral nervous system. It is characterized by muscle weakness, numbness, paralysis, or difficulty breathing. The exact cause of GBS is unknown, but it often occurs after an infection, such as a respiratory or gastrointestinal infection. Diagnosis of GBS involves a combination of clinical evaluation, NCV, and LP to analyze CSF. Treatment focuses on providing supportive care. This may include IVIG or plasmapheresis. It is a curable disease. Objectives: We carry out our study to determine the Frequency and Clinical features of Guillain Barré Syndrome among Patients of USTH from 2014 to 2023, Sana'a, Yemen, 2024.